Severe Neonatal Skin Infection: Clinical Case - Denis K. Efimov; Ekaterina A. Goncharova; Maria A. Khachaturyan; Tatyana V. Turti; Lyudmila M. Makarova (Педиатрическая фармакология)
Background. Pyoderma is the most common skin infectious disease of early age, it is a group of dermatoses characterized by purulent-inflammatory damage to the skin, dermal appendages, and subcutaneous fat. The diagnosis is based on medical history and physical examination. The main treatment methods are antibacterial therapy (local or systemic) and antiseptic skin toilet. Some forms of deep pyoderma require surgical interventions.Clinical case description. Girl A., 14 days of life, was admitted to the neonatal department of infectious disease with complaints of the mass in the left shoulder joint area. Historical information: 27 years old mother was not observed in any maternity welfare centre; chorioamnionitis was revealed at admission to the obstetric hospital. She received broad-spectrum antibacterial therapy perinatally. A girl from spontaneous vaginal delivery born on the 39th week with body weight of 2700 g, body length of 50 cm, and APGAR score of 8/9, she was breastfed. The condition on admission was severe. There were multiple indurated rash elements (pustules with turbid fluid) on the skin of the chest, limbs, and back. Skin desquamation was noted. There was hyperemia area up to 3.5 × 1.5 cm in the left shoulder joint area, with soft-elastic consistency, fluctuation symptom was positive. Complete blood count has shown: leukocytosis and neutrophilosis. Methicillin-resistant Staphylococcus aureus (MRSA) was revealed in blood via PCR method, in hemoculture, and in throat and nose cultures. C-reactive protein level was increased. Abscess culture — MRSA. Screening by immunological assay was performed to exclude primary immunodeficiency. Abscess incision and drainage were performed; 5 mL of thick yellow-green pus was obtained. Combination therapy with broad-spectrum antibiotic was carried out.Conclusion. There was positive dynamics on the administered therapy: the child condition was satisfactory, skin cleared of infectious rash, abscess was sanitized, laboratory parameters normalized, the child had no fever.